THE IMPACT OF RUSSIAN-CHINESE INTER-REGIONAL AND CROSS-BORDER COOPERATION ON ENTREPRENEURSHIP DURING THE GLOBAL ECONOMIC CRISIS - Xin Ran (Vestnik MGIMO-Universiteta, 2013)
The article is devoted to the issue of the impact of Russian-Chinese Inter-regional and Crossborder Cooperation on Entrepreneurship during the Global Economic Crisis. Currently, the two main directions of development of the economy is the economic globalization and regional economic integration. Inter-regional and cross-border cooperation between Russia and China - an important part of bilateral relations, as well as a significant factor in promoting socio -economic development of neighboring regions and business between the two countries. The year 2008 was difficult for the world. Against the backdrop of a slow recovery of the global economy after the financial and economic crisis, Russia and China jointly overcome the difficulties of post-crisis, deepen strategic partnerships and actively explore new areas of cooperation. The effect of cross border cooperation on entrepreneurial activity in the recent years is shown in the border areas, in which accumulate significant experiences of using the potential of entrepreneurship for the high dynamics of the economic growth. In the aftermath of the crisis, the Russian and Chinese governments actively strengthened their cooperation. This provided more opportunities for the further deepening of enterprise development. Within the framework of regular meetings between the two governments signed a series of agreements and contracts in the oil and gas industry, the coal industry, as well as in the nuclear power industry and in the field of high-speed rail train and automobile, etc. More opportunities for investment and a better business environment in the border areas promote enthusiasm in the entrepreneurial activity. To ensure the implementation of entrepreneurial potential is necessary to create a favorable legal and economic conditions for the intensive development of the business, stimulating the formation of the market structure and the competitive environment. Entrepreneurship plays an important role for the development of border areas. The active level of the business not only strongly influences the development of cross-border and inter-regional cooperation, but also for the development of the border areas. The bilateral economic cooperation is helpful for the improvement of social and economic situation in the border areas.